E-Trust and E-Service Quality as Determinants of E-Customer Loyalty on E-Commerce Platforms: a Case Study of Shopee - Ezha Gadis Rekly Arimbi; Siti Mujanah; Achmad Yanu Alif Fianto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The development of e-commerce in Indonesia has shown significant growth, particularly with the increasing use of mobile applications for transactions. Shopee, as one of the largest e-commerce platforms in Indonesia, has experienced a notable increase in market share across various demographic groups. However, market dominance does not automatically guarantee customer loyalty. This study aims to analyze the influence of electronic service quality (e-service quality) and electronic trust (e-trust) on electronic customer loyalty (e-customer loyalty) on Shopee. The method employed is a literature review with a qualitative descriptive-analytical approach, through the collection and synthesis of relevant previous studies. The analysis results indicate that e-service quality plays a crucial role in shaping positive customer perceptions through fast, accurate, and responsive services, while e-trust enhances customer confidence in the platform’s security, reliability, and transparency. Both factors significantly affect customer loyalty, either directly or through the mediation of customer satisfaction (e-satisfaction). This study contributes to the development of e-commerce strategies, particularly in enhancing digital experiences, building customer trust, and maintaining Shopee’s customer loyalty sustainably.